Educommunication and school radio in the fields of Boyacá. A perspective from Gadamer's hermeneutics (2021)
Objective: To analyze the meaning of educommunication and school radio as pedagogical tools for the development of rural education from the hermeneutic perspective of H. G. Gadamer. Originality/support: Globalization has brought new schemes of satisfaction within the teaching and learning process, and the use of communication and information technologies constitutes an accumulation of tools for the development of knowledge, which is why it is required that teachers in the Colombian countryside be at the forefront of a changing society and explore new pedagogical strategies that motivate students to assume new roles. Having said this, the research analyzes the sense that rural school teachers have about educommunication, allowing to make a contribution to the study of this category with a philosophical rigor centered on the Gadamerian hermeneutics.   Method: The research is structured from the qualitative paradigm with an interpretative approach, centered on the method of the hermeneutic circle from the perspective of Hans Georg Gadamer. Strategies/information collection: For the hermeneutic interpretation, the ATLAS.ti software is used, in which a hermeneutic unit is proposed with the categories: school fact, communication, pedagogical strategy and educommunication, which allow shaping the theoretical foundation, as well as the design and analysis of hermeneutic-interpretative matrices. Conclusions: The interpretation of the sense that the educator and the students of rural contexts have about the radio allows understanding, from the Gadamerian perspective, the method with which the impact of educommunication strengthens oral expression, psychological development and knowledge transfer, establishing a relationship of correspondence between them.